ChemInform Abstract: Lewis and Broensted Acid Induced (3 + 2)‐Annulation of Donor—Acceptor Cyclopropanes to Alkynes: Indene Assembly. Issue 28 (July 2015) - Rakhmankulov, Eduard R.; Ivanov, Konstantin L.; Budynina, Ekaterina M.; Ivanova, Olga A.; Chagarovskiy, Alexey O.; Skvortsov, Dmitriy A.; Latyshev, Gennadij V.; Trushkov, Igor V.; Melnikov, Mikhail Ya.
Abstract (3 + 2)‐Annulation of donor—acceptor cyclopropanes to alkynes induced by both Lewis and Broensted acids is developed.